Loss of Janus Associated Kinase 1 Alters Urothelial Cell Function and Facilitates the Development of Bladder Cancer - Daza-Cajigal, Vanessa; Albuquerque, Adriana S.; Pearson, Joanna; Hinley, Jennifer; Mason, Andrew S.; Stahlschmidt, Jens; Thrasher, Adrian J.; Mishra, Vibhash; Southgate, Jennifer; Burns, Siobhan O. (Frontiers in Immunology, 2019)
Inherited Primary Immunodeficiency (PID) disorders are associated with increased risk of malignancy that may relate to impaired antitumor immune responses or a direct role for PID germline mutations in tumorigenesis. We recently identified germline loss of function mutations in Janus Associated Kinase 1 (JAK1) causing primary immunodeficiency characterised by infections and associated with early onset, fatal high-grade bladder carcinoma. Somatic mutations in JAK1, required for immune cell signalling in response to interferon gamma (IFNγ), have been associated with several non-hematopoietic and hematopoietic cancer cell types but pathogenic mechanisms remain largely unexplored. Here we demonstrate that JAK1 is required for the intrinsic IFNγ response of urothelial cells impacting immunogenicity and cell survival. Specifically, JAK1-deficient urothelial cells showed reduced surface expression of major histocompatibility complex class II (MHC II), intercellular adhesion molecule-1 (ICAM-1) and programmed death-ligand-1 (PD-L1) after IFNγ stimulation and were resistant to IFNγ-induced apoptosis and lymphocyte-mediated killing. In addition, we identify a previously unknown role for IFNγ signalling in modulating urothelial differentiation. Together, our findings support a role for urothelial cell JAK1 in immune surveillance and development of bladder cancer. Our results have implications for patients with rare JAK1 PID and, more broadly, inform development of biomarker and targeted therapies for urothelial carcinoma.